2018
DOI: 10.1016/j.pediatrneurol.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Pediatric Neurocritical Care in the United States

Abstract: Background: Pediatric Neurocritical Care (PNCC) diseases affect thousands of children annually. We aimed to quantify the burden of PNCC through generation of national estimates of disease incidence, utilization of critical care interventions (CCI), and hospital outcomes. Methods: We performed a retrospective cohort analysis of the Kids Inpatient Database over three years to evaluate pediatric traumatic brain injury, neuro-infection or inflammatory diseases, status epilepticus, stroke, hypoxic ischemic injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…However, multiple domains were often affected (67% of patients with severe disability had changes in $3 separate domains). We found that nearly 1 in 10 PNCC admissions result in death, confirming results from previous administrative data and point-prevalence studies in PNCC 3,4 and showing that PNCC mortality is substantially higher than rates for other PICU cohorts. 12,19 We also found high rates of morbidity that were consistent with previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, multiple domains were often affected (67% of patients with severe disability had changes in $3 separate domains). We found that nearly 1 in 10 PNCC admissions result in death, confirming results from previous administrative data and point-prevalence studies in PNCC 3,4 and showing that PNCC mortality is substantially higher than rates for other PICU cohorts. 12,19 We also found high rates of morbidity that were consistent with previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…These patients frequently require critical care interventions, account for billions of dollars in annual hospital costs, and suffer high rates of mortality and morbidity. 4 However, quantification of detailed outcomes among many PNCC diagnoses is scarce and limits intervention research to improve outcomes for these vulnerable children.…”
mentioning
confidence: 99%
“…The six sources that were identified as reporting estimates of the annual incidence of SE in the USA were published between 1996 and 2018 and are shown in Table 3. The reported annual incidence of SE ranged from 3.5 to 41 per 100,000 [11][12][13][14][15][16]. Four studies reported estimates of annual incidence for all ages combined [11][12][13][14], one reported the incidence in an adult population (>20 years of age) [15], and one reported the incidence of SE in a pediatric population (≤20 years of age) [16].…”
Section: Incidence Estimatesmentioning
confidence: 99%
“…The reported annual incidence of SE ranged from 3.5 to 41 per 100,000 [11][12][13][14][15][16]. Four studies reported estimates of annual incidence for all ages combined [11][12][13][14], one reported the incidence in an adult population (>20 years of age) [15], and one reported the incidence of SE in a pediatric population (≤20 years of age) [16]. When considering age, the Richmond (Virginia) study revealed a bimodal (Ushaped) distribution of overall SE incidence with the highest estimates in the first years of life (0-4 years of age) and after 60 years of age [12].…”
Section: Incidence Estimatesmentioning
confidence: 99%
“…More than 500 000 pediatric patients present to the emergency department for traumatic brain injury and 50 000 require hospitalization in the United States each year. 1,2 From 2001 to 2012, the rate of emergency department visits for a diagnosis of traumatic brain injury or concussion more than doubled among children aged 19 years or younger. 3 Traumatic brain injury leads to a range of long-term morbidities including physical, psychosocial, and neurocognitive deficits.…”
mentioning
confidence: 99%